The Moderating Role Of Financial Rewards, Job Market, And Prestige On Public Accountant Career Interest - Anak Agung Ngurah Agung Kresnandra; Noviari, Naniek; I Made Andika Pradnyana Wistawan (E-Jurnal Akuntansi, 2025)
This study examines the influence of personality types on accounting students’ interest in pursuing a career as public accountants, considering the moderating roles of financial rewards, job market, and prestige. Respondents were seventh-semester undergraduate accounting students at the Faculty of Economics and Business, Udayana University, selected using purposive sampling. Data were collected through questionnaires and analyzed with classical assumption tests and Moderated Regression Analysis (MRA). The results indicate that personality types significantly affect students’ interest in becoming public accountants. Financial rewards do not moderate this relationship, whereas job market considerations and prestige do. These findings underscore the importance of external factors, particularly job market conditions and the profession’s image, in strengthening the impact of personality on students’ career choices as public accountants.